Respostas
respondido por:
2
Resposta:
a) olhar a imagem.
b) olhar a imagem.
c) f(-1)=1 e g(-1)=4
d) f(N) e g(-2, -1, 0, 1, 2, 3, 4, 5)
e) f(-1, -1/2, 0, 1/2, 1, 2) e g(-1, 0, 1/3, 2/3, 1)
f) f(N) e g(-2, -1, 0, 1, 2, 3, 4, 5)
Explicação passo-a-passo:
f(x)=2x+3
f(-1)=2.(-1)+3
f(-1)=-2+3
f(-1)=1
g(x)=-3x+1
g(-1)=-3.(-1)+1
g(-1)=3+1
g(-1)=4
Anexos:
![](https://pt-static.z-dn.net/files/d3b/f183f7308d46fbb7f6e271252f6b8a20.png)
Perguntas similares
5 anos atrás
5 anos atrás
5 anos atrás
8 anos atrás
8 anos atrás
8 anos atrás
8 anos atrás
8 anos atrás